Enhancing Cardiovascular Disease Literacy Through Healthy Lifestyle-Based Biology Learning: A Quasi-Experimental Study of High School Students in North Sumatra, Indonesia - Robert Harianja; Sariayu Sibarani (Jurnal Pendidikan Terapan, 2026)
Purpose: This study examines the effectiveness of healthy lifestyle-based biology learning in improving cardiovascular disease literacy among high school students in North Sumatra, Indonesia. Methods: A quasi-experimental pretest posttest control group design was employed involving 120 Grade XI students. The experimental group received biology learning integrated with experiential health activities (body mass index measurement, heart rate monitoring, dietary analysis, and cardiovascular simulations), while the control group received conventional instruction. Data were collected using a validated cardiovascular disease literacy test covering functional, interactive, and critical dimensions (α = 0.82). Data were analyzed using independent samples t-tests, ANCOVA, and normalized gain (N-gain). Findings: The results showed that the experimental group achieved significantly higher posttest scores than the control group (p < 0.001), with a large effect size (Cohen’s d = 0.92). Literacy improvements were observed across functional, interactive, and critical dimensions, all within the moderate N-gain category. In addition, students demonstrated positive behavioral changes, including reduced sedentary time and increased daily physical activity. Conclusion: Healthy lifestyle-based biology learning is effective in enhancing adolescents’ cardiovascular disease literacy and promoting healthier lifestyle behaviors. Integrating experiential health activities into biology instruction provides a practical approach to strengthening preventive health education in schools. Implications: The study highlights the potential of curriculum-integrated health education to address early risk factors of non-communicable diseases among adolescents. Ethical approval was obtained, and informed consent was secured from all participants and their guardians.